Mood Sensitivity to Seasonal Changes in African College Students Living in the Greater Washington D.C. Metropolitan Area - Alvaro Guzman; Kelly J. Rohan; Samina M. Yousufi; Minh-Chau Nguyen; Michael A. Jackson; Joseph J. Soriano; Teodor T. Postolache (The Scientific World Journal)
The purpose of this study was to estimate the degree of seasonality and prevalence of winter- and summer-type seasonal affective disorder (SAD) in African immigrant college students in comparison with African American peers. A convenience sample of 246 African immigrants and 599 African Americans studying in Washington, D.C. completed the Seasonal Pattern Assessment Questionnaire (SPAQ), which was used to calculate a global seasonality score (GSS) and to estimate the prevalence of winter- and summer-type SAD. Degree of seasonality was related to a complex interaction between having general awareness of SAD, ethnicity, and gender. A greater percentage of African students reported experiencing a problem with seasonal changes relative to African American students, and had summer SAD, but the groups did not differ on GSS and winter SAD. African students reported more difficulties with seasonal changes than their African American peers, which could represent a manifestation of incomplete acclimatization to a higher latitude and temperate climate. As Africans also had a greater rate of summer SAD, this argues against acclimatization to heat.